Experiential Value in Multi-Actor Service Ecosystems: Scale Development and Its Relation to Inter-Customer Helping Behavior - Weretecki, Patrick; Greve, Goetz; Henseler, Jörg (Frontiers in Psychology, 2021)
Interactions in service ecosystems, as opposed to the service dyad, have recently gained much attention from service research. However, it is still unclear how they influence customers’ experiential value and trigger desired behavior. The purpose of this study is to identify which elements of the multi-actor service ecosystem contribute to customers’ experiential value and to investigate its relation to customers’ interaction attitude and inter-customer helping behavior. The authors adopted a scale development procedure from the existing literature. Service, brand, retail and tourism management research as well as expert feedback is used to generate a pool of 33 items. Exploratory and confirmatory factor analysis were conducted. The scale was validated based on more than 468 responses to a CASI at one of the world’s largest trade shows. Scale-development procedure was followed by structural equation modeling. Confirmatory factor analysis supports that experiential value in multi-actor ecosystems comprises five dimensions. The functional value of personnel (professionalism), the perception of other customers’ appearance (similarity), the perception of other customers’ behavior (suitable behavior), multisensory stimuli (sensory appeal) and customers’ enjoyment (playfulness). Experiential value positively and directly relates to customers’ interaction attitude and inter-customer helping behavior. Furthermore, experiential value indirectly relates to inter-customer helping behavior, mediated by interaction attitude. Managers interested in getting more out of interactions with customers will develop an understanding for the interplay between the physical environment and individuals within a multi-actor ecosystem. They can use the scale to assess experiential value, encourage customers’ interaction attitude and utilize customers’ influence on their peers. This paper synthesizes insights from existing research on experiential value, from various fields, in one scale. This holistic approach is the first to simultaneously account for customers’ interactions with the multisensory physical environment, their personal interactions with employees and interactions between customers in a multi-actor service ecosystem.